2018
DOI: 10.21577/0103-5053.20180047
|View full text |Cite
|
Sign up to set email alerts
|

Full Factorial Experimental Design for Carbamazepine Removal Using Electrochemical Process: a Case Study of Scheming the Pathway Degradation

Abstract: Carbamazepine is an antiepileptic drug which is considered one of the persistent compounds detected in Malaysian aquatic environment. In this present study, a full factorial experimental design was applied for the analysis of effect NaCl amount, initial concentration of carbamazepine, applied voltage and treatment time on the electrochemical removal percentage of carbamazepine. However, applied voltage was found as the most significant factor with p = 0.00 lower than 95% confidence level. The investigation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This means that sepiolite may be employed as an ion-exchanger to remove lead due to its cation-exchange capacity [38]. The TCLP provided more acidic conditions for the lead smelting slag than the DIN [48]. The removal of lead as a function of the adsorbent type and the adsorbent dosage is given in Figure 9b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that sepiolite may be employed as an ion-exchanger to remove lead due to its cation-exchange capacity [38]. The TCLP provided more acidic conditions for the lead smelting slag than the DIN [48]. The removal of lead as a function of the adsorbent type and the adsorbent dosage is given in Figure 9b.…”
Section: Resultsmentioning
confidence: 99%
“…The pH of the TCLP extraction fluid was around 4.93 ±0.05. Therefore, the TCLP provided more acidic conditions for the lead smelting slag than the DIN [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that drugs electrochemical degradation has been reduced with increasing the initial concentration of selected compound (Al-Qaim et al 2018b;Mussa et al 2018).…”
Section: Effect Of Initial Hdx-cbz Concentrationmentioning
confidence: 99%